2011
DOI: 10.1007/s10886-011-9954-z
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Defensive Characteristics in the Phloem of Ash Species Resistant and Susceptible to Emerald Ash Borer

Abstract: We examined the extent to which three Fraxinus cultivars and a wild population that vary in their resistance to Emerald Ash Borer (EAB) could be differentiated on the basis of a suite of constitutive chemical defense traits in phloem extracts. The EAB-resistant Manchurian ash (F. mandshurica, cv. Mancana) was characterized by having a rapid rate of wound browning, a high soluble protein concentration, low trypsin inhibitor activities, and intermediate levels of peroxidase activity and total soluble phenolic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
88
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(101 citation statements)
references
References 30 publications
11
88
2
Order By: Relevance
“…Phenolic and Lignin Extraction Soluble phenolics were extracted according to Eyles et al (2007) and Cipollini et al (2011). Extracts were stored at −20º C and used in subsequent HPLC analyses within 3 wk following extraction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Phenolic and Lignin Extraction Soluble phenolics were extracted according to Eyles et al (2007) and Cipollini et al (2011). Extracts were stored at −20º C and used in subsequent HPLC analyses within 3 wk following extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was noted that constitutive phenolic compounds, including hydroxycoumarins and phenylethanoid glycosides (calceolariosides A and B), were found in phloem tissue of Manchurian ash but not in green and white ash. These compounds were hypothesized to contribute to the high resistance of Manchurian ash to EAB (Eyles et al, 2007;Cipollini et al, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that these two unrelated species modify soils in ways with very similar consequences for subsequent plant growth. It is known that some aspects of their secondary chemistry are similar [18,50]. In fact, Fraxinus is invasive in Hungary where research showed evidence of reduced germination rates and growth of white mustard (Sinapis alba L.) caused by green ash extracts [51].…”
Section: Conspecific Versus Heterospecific Feedbacks and Allelopathymentioning
confidence: 99%